The Diffusion Coatings for Industrial Tool Application - Drajewicz, Marcin; Przybylo, Adrianna; Jopek, Jakub; Góral, Marek; Koscielniak, Barbara; Ochal, Kamil; Kubaszek, Tadeusz; Gurak, Artur; Dychton, Kamil; Wozniak, Mateusz; Kwasniewski, Pawel; Kawecki, Artur; et al. (Manufacturing Technology Journal, 2022)
The diffusion boriding process allows to increase the abrasion and corrosion resistance of the majority of steel grades. The aim of this study was to determine the influence of the chemical composition of the substrate of various steel grades on the microstructure of boride coatings produced using two diffusion methods: pack cementation boriding using EKABOR-2 and paste-pack boriding using EKABOR-PASTE on the substrate of tool and structural steels:. The boriding processes were carried out at 1000oC in an argon atmosphere for 4h. Scanning microstructure investigations of the obtained coatings indicate that a high content of alloying elements increasing the FeB (Cr, Mo, W) phase, results in the formation of an external, continuous layer of FeB borides. It was found that with increasing alloying element and carbon concentration, the total thickness of the boride coatings decreases. In particular, a chromium content below about 1%, with a carbon content below about 0.4%, significantly limits or prevents the formation of the FeB phase. Increasing the content of alloying elements and carbon, results in a change in the morphology of the iron borides.
Keywords: Boride coatings; Hard coatings; Pack boriding; Wear; Corrosion